Tilapia by-product meal in rations for Nile tilapia (Oreochromis niloticus) fingerlings - Feiden, Aldi; Boscolo, Wilson R.; Signor, Altevir; Signor, Arcangelo A.; Reidel, Adilson (Semina: Ciências Agrárias, 2005)
Objectifying to evaluate the inclusion of tilapia processing residues (FT) in the feeding of Nile tilapia (Oreochromis niloticus) fingerlings, 125 Nile tilapia fingerlings (with average initial weight of 0.72Â±0.19g) were distributed in a completely randomized design with five treatments and five repetitions in 25 aquariums (30L). The rations were formulated to contain 0, 5, 10, 15% of FT and 0% FT plus methionine (0+met). Isoproteics, isocalcitics, isophosphorics and isoenergetics diets were used. After 28 days of experiment, final weight (PF), weight gain (GP), feed conversion ratio (CA) and survival (SO), were evaluated. No differences were observed (P>0.05) for the studied parameters. It was concluded that the FT can be used up to 15% in substitution to the soybean meal in the diet of nile tilapia fingerlings.